Criteri di priorità per l’allocazione di risorse sanitarie scarse nel corso della pandemia da CoViD-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The SARS-CoV-2 virus pandemic has highlighted a serious shortage of health resources, which in this work is analyzed with reference to the specific context of Italy. The ethical principles and values that, from time to time, have justified the priority criteria for the allocation of scarce health resources in three areas are examined: territorial assistance, triage for admission to ICU, scarcity of CoViD-19 vaccines. The argument concludes that the prevalence of the public "benefit" in pandemic circumstances involves a change of perspective but does not require the change of the ethical-regulatory paradigm that structures the National Health Service in Italy.
Keywords: CoViD-19; public ethics; solidarity; health resources allocation; ICU triage